Insecticidal activity of monoamide compounds from Humulus scandens against Spodoptera frugiperda - Liu, Yuxuan; Wu, Xiaoyun; Li, Fengchao; Qin, Deqiang; Gao, Xi; Wu, Guoxing; Qin, Xiaoping (Frontiers in Plant Science, 2025)
Spodoptera frugiperda, a globally invasive pest, currently lacks effective control measures beyond certain chemical pesticides. Previous reports have demonstrated the effectiveness of Humulus scandens against various agricultural pests. Here, our aim was to derive toxic compounds and explore the insecticidal potential of the botanical plant H. scandens against S. frugiperda. Through activity-guided isolation, two monoamide compounds, N-p-coumaroyl tyramine (1) and N-trans-feruloyl tyramine (2), were identified from the EtOAc extract of H. scandens. The results showed that both compounds 1 and 2 exhibited good insecticidal effects on S. frugiperda under both contact and dietary toxicity methods, with significant dose-dependent effects; however, compound 2 demonstrated stronger insecticidal activity. On the other hand, both compounds exhibited stronger contact toxicity than ingestion toxicity, with compound 2 having an LC50 (50% lethal concentration) of 47.97 μg/mL. Insecticidal mechanism studies revealed that both compounds act on the acetylcholinesterase (AChE) of S. frugiperda, with compound 2 showing stronger inhibition (50% inhibitory concentration, IC50 = 19.71 ± 1.98 μg/mL). Kinetic studies of the compounds on AChE indicated that both monoamides are reversible competitive inhibitors of AChE, with Ki values of 23.76 μg/mL and 20.79 μg/mL, respectively. This study revealed the active insecticidal compounds from H. scandens and their mechanisms of action. These findings provide new insights into the secondary metabolites of H. scandens which may serve as a basis for the development of novel plant based insecticides. Furthermore, these results suggested the use of these two bioactive compounds in the integrated management of S. frugiperda as alternatives to synthetic insecticides.